Entomofaunistic diversity of arthropods in cucumber farming (Cucumis sativus L.) - Leonardo Severgnini; Rafael Dal Bosco Ducatti; Dannyelle Cristine Orsolin de Morais; Siumar Pedro Tironi; André Luiz Radünz; Marco Aurélio Tramontin (Acta Biológica Catarinense, 2019)
Cucumber (Cucumis sativus Linnaeus, 1753) stands out in the Brazilian agribusiness of vegetables as it can be consumed in salads (in natura or pickled) or even used for the production of cosmetics and drugs. During cucumber cultivation, several insectpests, mainly from the Orders Hemiptera, Thysanoptera, Lepidoptera, can cause significant yield losses. Therefore, this study aimed to evaluate the entomofaunistic diversity of arthropods in cucumber crop using Moericke and Pitfall traps. Cucumber seedlings were commercially obtained and grown up in the experimental area of the Federal University of Fronteira Sul – Campus Chapecó (SC). Three samplings were carried out between October and December, 2015. The sampled specimens were identified to the taxon of Order and placed in vials containing alcohol solution (70%). A total of 1.651 specimens were identified and classified into 11 different Orders. Pitfall traps sampled a greater number of orders (9) and specimens (1.309), with emphasis to the Order Hymenoptera (928). For the aerial traps (Moericke), 342 specimens, allocated in eight different Orders, were identified, with the Order Diptera as the most abundant one (153 individuals). Moericke and Pitfall traps showed a Shannon-Weaver diversity index of 1.53 and 1.02, respectively.